Relationship between the structure and composition of rumen microorganisms and the digestibility of neutral detergent fibre in goats - Kaizhen Liu (Asian-Australasian Journal of Animal Sciences, 2019)
Objective This experiment was conducted to compare the structure and composition of ruminal microorganisms in goats with high and low neutral detergent fibre (NDF) digestibility. Methods Nineteen crossbred goats were used as experimental animals and fed the same total mixed rations during the 30-day pre-treatment and 6-day digestion trialperiods. All faeces were collected during the digestion period for measuring the NDF digestibility. Then, high and the low NDF digestibility individuals were chosen for the high NDF digestibility group (HFD) and low NDF digestibility group (LFD), respectively. Rumen contents were collected for total microbial DNA extraction. The V4 region of the bacterial 16S rRNA gene was amplified using universal primers of bacteria and sequenced using high-throughput sequencer. The sequences were mainly analysed by QIIME 1.8.0. Results A total of 18,694 operational taxonomic units were obtained, within 81.98% belonged to bacteria, 6.64% belonged to archaea and 11.38% was unassigned microorganisms. Bacteroidetes, Firmicutes, and Proteobacteria were the predominant microbial phyla in both groups. At the genus level, the relative abundance of fifteen microorganisms were significantly higher (p<0.05) and six microorganisms were extremely significantly higher (p<0.01) in LFD than HFD. Overall, 176 core shared genera were identified in the two groups. The relative abundance of 2 phyla, 5 classes, 10 orders, 13 families and 15 genera had a negative correlation with NDF digestibility, but only the relative abundance of Pyramidobacter had a positive correlation with NDF digestibility. Conclusion There were substantial differences in NDF digestibility among the individual goats, and the NDF digestibility had significant correlation with the relative abundance of some ruminal microorganisms.